Ant colony approach to intelligent auto-recovery in manufacturing - Aung Sann Win (2008)
In this thesis, a path-finding algorithm for self-recovery of MHS in manufacturing is developed based on the Ant Colony System (ACS) algorithm. ACS is an algrithm in which a set of artificial ants, also called agents, cooperates to find a solution of a problem by exchanging pheromone information.